PARADIGMA AL-QUR’AN TENTANG NARASI SIKSAAN - Desri Ari Enghariano (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Talking about torture, what humans can imagine is a very painful disaster inflicted by Allah SWT on humans in return for their actions. The question always arises in everyone's mind, whether natural disasters and accidents in our transportation world have been planned by Allah? Is natural disaster a test, a blessing or a torment?This research is library research, namely research using written materials, such as books, journals, magazines, and so on. This research is a qualitative research of interpretation and presentation of data by means of descriptive-analytic method. Thematic method is the choice in completing this research. The results of this research explain that the meaning of torture is a warning of Allah's wrath on his creatures (humans) who have violated Allah's commands. torment said with all the fractions the word is mentioned in the Qur'an 374 times. The cause of torment or calamity is because of denying the verses of Allah. A proportional attitude in the face of torment is to istighfar and be patient.